A Comparative Study of Academic Performance in Myopic Students With and Without Vision Correction - Erfira, Erfira; Febriandriani, Dini; Farida, Nida; Mahrunnisa, Fitria; Ulfah Irawati, Nur Bebi; Hermawati, Luluk; Usman, Muhammad (The Avicenna Medical Journal, 2025)
Background: Vision is the primary way people get information and is crucial for the learning process. The World Health Organization (WHO) reports that 285 million people worldwide are visually impaired, with 42% of cases due to uncorrected refractive errors. School-age children are highly vulnerable to refractive errors, with myopia (nearsightedness) being the most common. A decrease in visual function due to myopia interferes with tasks requiring far vision, such as reading the blackboard, which can negatively impact academic performance. This study aims to compare the academic performance of patients with corrected and uncorrected myopia. Methods: This was a cross-sectional analytic study of 5th-grade elementary school students with myopia in Jakarta during 2023. Data collected included the students' average mid-semester exam scores and their myopia status, determined by visual acuity examinations. Results: Out of 106 respondents, 34% (36 people) had corrected myopia and 66% (70 people) had uncorrected myopia with 35 (33%) respondents having academic performance results below the passing grade. Bivariate analysis of the data using the Chi-square test yielded a p-value of 0.010 (p < 0.05). Conclusion: There is a significant relationship between academic performance results and the incidence of myopia.